2010
DOI: 10.2478/s11532-010-0053-8
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-liquid equilibrium of novel aqueous two-phase systems and evaluation of salting-out abilities of salts

Abstract: Binodal data are beneficial to the design of aqueous two-phase extraction and the establishment of thermodynamic models. For the 2-propanol + Li 2 SO 4 /Na 2 SO 4 / (NH 4 ) 2 SO 4 /K 3 PO 4 + water systems and 1-propanol + K 3 PO 4 /K 3 C 6 H 5 O 7 /(NH 4 ) 3 C 6 H 5 O 7 + water systems, binodal data were determined at 298.15 K. The binodal data were correlated by a theoretical equation on the basis of statistical geometry. The salting-out abilities of salts and the phase-separation abilities of alcohols were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 14 publications
3
20
0
5
Order By: Relevance
“…As a result, relatively a lesser concentration of sodium citrate is needed to form a two-phase system as compared to other salts. Recently, comparable results were obtained by Wang et al [39] and concluded that the EEV of Sodium sulfate > Ammonium sulfate and Potassium citrate > Ammonium citrate.…”
Section: Isrn Chemical Engineeringsupporting
confidence: 77%
See 1 more Smart Citation
“…As a result, relatively a lesser concentration of sodium citrate is needed to form a two-phase system as compared to other salts. Recently, comparable results were obtained by Wang et al [39] and concluded that the EEV of Sodium sulfate > Ammonium sulfate and Potassium citrate > Ammonium citrate.…”
Section: Isrn Chemical Engineeringsupporting
confidence: 77%
“…Effective excluded volume characterizes the acceptableness of a particular salt by the hydrophilic polymer, PEG with water as a solvent to form an ATPS. It has been cited in the literature that increase in EEV value, increases the salting-out ability of a salt [39]. Hence, herein we made an attempt to explain the binodal behavior with respect to EEV.…”
Section: Isrn Chemical Engineeringmentioning
confidence: 95%
“…From Table 7, the EEV value of 1-propanol-NaOH system is larger than that of 2-propanolNaOH system at the same temperature, which indicates that the phase-forming strength of 1-propanol is stronger than 2-propanol. The acting force between alcohols themselves is in the order 1-propanol > 2-propanol > ethanol, which can explain the phaseforming abilities of the investigated hydrophilic alcohols [23].…”
Section: Effective Excluded Volume Theorymentioning
confidence: 99%
“…Liquid-liquid equilibria (LLE) are the key in improving the performance of an extraction process and understanding the phase behavior of systems exhibiting two liquid phases 12 . Only a few reports found in the literature focus on the study of ternary systems composed by 2-propanol +Na 2 SO 4 / (NH 4 ) 2 SO 4 + H 2 O systems [9][10] . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our knowledge, there are only two works in the literature describing phase diagrams of ternary systems composed by 2-propanol+(NH 4 ) 2 SO 4 + +H 2 O 9 and 2-propanol+Na 2 SO 4 /(NH 4 ) 2 SO 4 +H 2 O 10 . None of these reports have conducted a systematic study on the phase-formation ability of the sulfate salts in hydrophilic alcohol + salt + water systems.…”
Section: Introductionmentioning
confidence: 99%